Clto open heart as operative treatment of foreign body In the left ventricle removal - M. Rosadi Seswandhana M. Rosadi Seswandhana (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2003)
Foreign body in the left ventricle is rare and it is associated most commonly with significant trauma. The diagnosis of a foreign body in the left ventricle can be difficult. One must distinguish between foreign matter in the cardiac chamber or free-floating in the mediastinum. Our case was male, 38 years old. He presented not only with typical complaints of chest pain and dyspnea, but also with the complaint of a "foreign body" in the right of his chest after a work accident. Physical examination and serial chest X-rays on the earlier survey showed right hemothorax and foreign body appearance on the back wall of the heart. Insertion of chest tube with water sealed drainage was done as a primary treatment. On the echocardiography and fluoroscopy examination, we found foreign body appearance in the left ventricle. To prevent myocarditis, either sterile or non-sterile, with potential for other significant complications, removal of an intraventricle foreign body is always indicated. Cito open heart with heart-lung machine was performed to extract the foreign body. There was no complication after 7 month evaluation.Key words: Foreign body removal - In the left ventricle - Work accident - Cito open heart